Evaluation of Corpus Luteum Vascularization in Recipient Mares by Using Color Doppler Ultrasound - Azevedo, Marlon de Vasconcelos; Souza, Natália Matos; Sales, Felipe Augusto Boudoux Martins; Ferreira-Silva, José Carlos; Chaves, Maiana Silva; Vieira, Joane Isis Travassos; Santos Filho, José Pompeu; Oliveira, Marcos Antonio Lemos (Acta Scientiae Veterinariae, 2021)
Background: Embryo transfer is one of the most commonly used reproductive biotechnique. The success of embryo transfer is also affected by the synchrony of estrus and ovulation between donor and recipient animals. In horse reproduction, ultrasonography has been used, among other purposes, to diagnose early pregnancy. However, only the color Doppler imaging mode makes it possible to evaluate the vascular architecture and the hemodynamic aspects of the vessels in several organs, especially the corpus luteum. The objective of this study was to evaluate, based on the color Doppler ultrasound, the corpus luteum vascularization and function from recipient mares at embryo transfer timing. Materials, Methods & Results: Mangalarga Machador mares from 5 to 10-year-old and a range of live weights of between 350 to 450 kg were used for this experiment, kept in pasture-based on mombaça grass (Panicum maximum) and were given ad libitum access to water and mineral supplementation. The animals (n = 15) were gynecologically examined and uterine consistency was evaluated by rectal palpation the same operator using an ultrasound system (SonoScape®) with a linear transducer, and operating frequency ranging from 5 to 10 Mhz. The uterine tone was classified between grades 1 and 4 and subjected to ovulation induction. The objective and subjective vascular perfusion of the corpus luteum was evaluated by color Doppler ultrasound on the day of embryo transfer and endometrium. The determination progesterone concentration on the day of the embryo transfer was performed by direct chemiluminescence assay. The arcsine (√P/100) transformation was applied to the percentage data, and the results were expressed as mean (.) ± standard error of the mean (SEM). Further, the assumptions of normality and homoscedasticity were verified, respectively, based on the Shapiro-Wilk and Lilliefors tests. Regarding the parametric and non-parametric variables, were applied, respectively, analysis of variance (ANOVA) followed by Tukey’s test, and the Kruskal-Wallis test followed by Dunn’s test. Pearson’s correlation coefficient was used to evaluate the relationship between the parameters. The statistical program SPSS 16.0 was used to perform the over-mentioned analyses, and a p-value < 0.05 was taken as significant. Corpus luteum vascular perfusion, based on the objective and subjective evaluation methods, and the progesterone concentration were higher in the pregnant mares (P < 0.05). The objective and subjective methods for evaluation of the vascular perfusion in the corpus luteum were positively correlated between themselves as well as to progesterone concentration (P < 0.05). There was no significant difference between the groups considering the uterine tonus evaluation (P > 0.05). Discussion: Mares that later became pregnant showed a higher concentration of progesterone as an outcome of the higher vascularization in the corpus luteum. It can be supported by both the correlation between the progesterone concentration and the corpus luteum vascular perfusion, as well as by the higher values of the vascular perfusion in pregnant mares. Based on the results, it has been concluded that the color Doppler ultrasound evaluation is an accurate tool to determine the corpus luteum vascularization, whether considering the objective or subjective methods. Also, the vascular perfusion is the most efficient parameter to determine both the corpus luteum function and to predict the ability of the recipient mares to maintain pregnancy.